Purpose, practice and theory: Teacher educators' beliefs about professional experience - Morrison, Chad (Social Science Press, 2016)
The purposes of professional experience within initial teacher education programs are varied (Russell, 2005). However, there is limited literature explaining (a) university-based teacher educators' beliefs about its purposes and (b) how these purposes are reflected in practice. This study investigated these themes. A pragmatic mixed-method research design (Tashakkori & Teddlie, 2010) was developed to survey teacher educators from one Australian and one New Zealand university (n = 56). Participants were anonymously surveyed using a diamond ranking activity (requiring placement of 9 of 11 professional experience purpose statement cards, pre-determined from literature) and open response items seeking explanations of placement determining criteria and statement elimination. Following analysis of questionnaire data, focus groups were utilised to further explore the aggregated findings. Survey data were analysed by weighting frequencies of each statement. Analysis of the data indicated significant variation of perspectives amongst the teacher educators and resulted in the clustering of purposes into four groups. This paper presents these data from the Australian university cohort (n = 26). This study, the first of a series designed to elucidate understandings of teacher educators' purposes for professional experience, reinforces the importance of professional experience as authentic workplace learning within initial teacher education. The findings also reveal the complex beliefs that underpin teacher educators' practices when preparing, mentoring and supervising preservice teachers for and within professional experience.